Densidade mineral óssea de perus de corte vacinados e não vacinados contra coccidiose - Paz, Ibiara Correia de Lima Almeida; Milbradt, Elisane Lenita [UNESP]; Mendes, Ariel Antonio [UNESP]; Vulcano, Luiz Carlos [UNESP]; Martins, Márcia Regina Fernandes Boaro [UNESP]; Komiyama, Claudia Marie [UNESP]; Cavichiolo, Fabiana; Garcia, Rodrigo Garófallo (My University, 2009)
It was evaluated bone mineral density of turkeys submitted the vaccination against coccidiosis. Used 420 turkeys of one day, divided in 4 treatments with 5 repetitions: T1 – control diet; T2 - diet and anti coccidiosis drugs; T3 - diet and commercial vaccine; T4 - diet and recombinant vaccine. To the 28 days the birds had been submitted to the challenge of coccidiosis, carried through inoculation of oocisty talked back directly in the esophagus of the birds. The bone quality was evaluated to the 21, 35, 49 and 72 days of age. For this, 8 birds for treatment had been collected, in each age of collection that had been sacrificed by cervical displacement. The tibiae and femura had been radiographed and tomographed for evaluation of the bone density, had been later evaluated texts of dry substance, bone ashes, calcium and of phosphorus. It had differences only between the ages, being that the treatments had not caused alterations of the bone characteristics. To the 56 days the birds had presented bone quality worse. The treatments had not influenced the studied parameters. What it allows to conclude that the vaccination against coccidiosis promotes good mineralization of the bones.

Avaliou-se a densidade mineral óssea de perus de corte submetidos a vacinação contra cocidiose. Utilizou-se 420 perus de corte de um dia, divididos em 4 tratamentos com 5 repetições: T1 – dieta controle; T2 – dieta e drogas anticoccidianas; T3 – dieta controle e vacina comercial; T4 – dieta controle e vacina recombinante. A vacinação foi realizada via ração, no oitavo dia de vida das aves, que foram alojadas com densidade recomendadas no manual da linhagem. Aos 28 dias as aves foram submetidas ao desafio de coccidiose, realizado inoculação de oocistos replicados diretamente no esôfago das aves. A qualidade óssea foi avaliada aos 21, 35, 49 e 72 dias de idade. Para isso, foram coletadas 8 aves por tratamento, em cada idade de coleta, que foram sacrificadas por deslocamento cervical. As tíbias e os fêmures foram radiografados e tomografados para avaliação da densidade óssea, posteriormente foram avaliados os teores de matéria seca, cinzas ósseas, cálcio e de fósforo. Houve diferenças apenas entre as idades, sendo que os tratamentos não causaram alterações das características ósseas. Aos 56 dias as aves apresentaram pior qualidade óssea. Os tratamentos não influenciaram os parâmetros estudados. O que permite concluir que a vacinação contra coccidiose promove boa mineralização dos ossos.
Bone mineral density in turkeys with vaccination and without vaccination against coccidiosis
Keywords: Coccidiosis; Turkeys; Bone quality; Vaccine; Coccidiose; Peru; Qualidade óssea; Vacina